Hemoglobin mass and iron status in athletes residing at moderate altitude - Goodrich, J. A. (University of Colorado Boulder, 2020)
Maximal aerobic power, or VO2max, is important for performance in a variety of sports. One of the primary parameters influencing VO2max is total hemoglobin mass (Hbmass) since it sets the upper limit for arterial oxygen carrying capacity. This dissertation examined how factors including arterial saturation, body composition, iron status, and training status influence Hbmass and therefore arterial oxygen carrying capacity in athletes at moderate altitude (1,625m).First, we examined whether oxyhemoglobin desaturation (DeltaSaO2) at VO2max modified the relationship between Hbmass and VO2max. In endurance athletes at moderate altitude, the relationship between Hbmass and VO2max was similar to that observed at sea level (r=0.94). However, correcting Hbmass by DeltaSaO2did not enhance this relationship (r=0.93), despite significant variability in DeltaSaO2; this raises the possibility that Hbmass and exercise-induced DelteSaO2 are not independent in endurance athletes. Next, in two separate cohorts of collegiate athletes, we examined factors that could influence Hbmass, with a focus on iron deficiency (ID). The first cohort included athletes from several team and individual sports as well as recreationally active controls. We found that Hbmass was more closely related to lean mass (r2=0.90) than body mass (r2=0.69), and after accounting for lean mass and sex, Hbmass was higher in endurance athletes and lower in ID individuals. The second cohort of athletes consisted of highly trained collegiate runners, and we found that ID was less common in NCAA national-championship qualifiers vs. non-qualifiers. In both cohorts, ID was common, and females were at elevated risk compared to males; however, the first cohort indicated that risk of ID was not different between athletes and non-athletes. Both cohorts provided evidence that ID in athletes is not driven by elevations in hepcidin or inflammatory cytokines, including IL-6. Overall, Hbmass is important to arterial oxygen carrying capacity, and is influenced by sex, lean mass, endurance training, and ID. Females are at higher risk for ID than males, and since ID can influence iv Hbmass and potentially competitive status, future research should focus on strategies to prevent ID. This dissertation illustrates that Hbmass could be a valuable addition to the hematological monitoring of athletes.